Indicators For the Analysis of Investment Efficiency In Oil and Gas Industry - Marius BULEARCĂ; Cornelia NEAGU; Daniel FISTUNG; Cristian SIMA (Communications of International Proceedings, 2023)
As part of a larger research that deals with modeling different aspect concerning oil and gas industry, this paper explores the possibilities of building up indicators for the analysis of investment efficiency in oil and gas industry aiming mainly at efficiency indicators, the influence of oil investments on the growth of national income, the influence of investments on production growth, and other indicators. Hence, in the beginning, a special focus is placed on revealing some models that may help us estimate the efficiency indicators in oil and gas industry, by introducing different indicators such as the effectiveness indicator of exploitation drilling, the economic effectiveness of the funds spent on exploitation wells, and the effectiveness of new wells entering production. Then, the paper analyzes the influence of oil investments on the growth of national income, with the aid of some specific indicators, such as the increase in national income per monetary unit invested and the increase in production value. The remaining part of the paper largely discusses upon the influence of investments on production growth, both in extraction and oil processing, and the influence of the volume of initial investments, on one hand, and the influence of the size of the working capital, on the other hand.
Keywords: oil and gas reserves; oil and gas wells; efficiency indicators; investment efficiency; economic effectiveness; production growth.